The Kubilius inequality in the polynomial semigroup - Bareikis, Gintautas (Lietuvos matematikos rinkinys, 2024)
Let P be a set of primary irreducible polynomials and Qm = p + 1; p ∈ P , ∂(p) = m. Kubilius inequality for additive functions f : Qm → C is proved.